CD4+ cell count responses to antiretroviral therapy are not impaired in HIV-infected individuals with tuberculosis co-infection. (17th July 2015) - Gupta, Rishi K.; Brown, Alison E.; Zenner, Dominik; Rice, Brian; Yin, Zheng; Thomas, H. Lucy; Pozniak, Anton; Abubakar, Ibrahim; Delpech, Valerie; Lipman, Marc
Abstract : Objective: To investigate whether HIV-infected individuals diagnosed with tuberculosis (HIV-TB) around the time of starting antiretroviral therapy (ART) have impaired CD4 + cell responses to treatment. Design: Analysis of a national cohort of HIV-infected adults, linked to the national TB surveillance system for England, Wales and Northern Ireland, including individuals starting ART from 2005 to 2009. Methods: We compared CD4 + cell responses in HIV-infected individuals starting ART with a TB diagnosis ('HIV-TB cohort') with those not known to have TB ('TB-free cohort'). The TB-free cohort was frequency-matched to the HIV-TB cases for sex, age strata, baseline CD4 + strata and ethnicity. Median change in CD4 + cell count from baseline (ΔCD4 + ) was calculated at 6-monthly intervals until 36 months. Results: There were 593 and 1779 individuals in the HIV-TB and TB-free cohorts, respectively (median follow-up 3.8 years). In both cohorts, median age was 36 years, 49.2% were women and 74.9% were black-African. Median baseline CD4 + at the start of treatment was similar in the HIV-TB and TB-free cohorts (74 vs. 80 cells/μl). Median ΔCD4 + was similar in HIV-TB and TB-free cohorts at all time points [294 (inter-quartile range 198–424) cells/μl in HIV-TB cohort; 296 (inter-quartile range 196–431) cells/μl in TB-free cohort after 3 years of ART]. A higher proportion of the HIV-TB cohort than the TB-free cohort died during follow-up (4.2 vs. 2.2%; P  = 0.01); 78.5% of all individuals who died had a baseline CD4 + cell count below 100 cells/μl. Conclusions: Long-term CD4 + cell recovery during ART appears similar in HIV-TB and TB-free patients. Significant mortality in both cohorts highlights the need for earlier HIV diagnosis and ART initiation. Abstract : Supplemental Digital Content is available in the text